2001
DOI: 10.1136/bjo.85.12.1421
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological examination of two cases of anterior staphyloma associated with Peters' anomaly and persistent hyperplastic primary vitreous

Abstract: Aims-To clarify the developmental mechanism and critical period for the uncommon complex of Peters' anomaly and persistent hyperplastic primary vitreous (PHPV). Methods-Two eyes with Peters' anomaly and PHPV were histologically examined by serial section. One eye was enucleated at age 7 months (case 1) and the other at age 4 months (case 2) owing to severe anterior staphyloma. Results-In both eyes, defects in the endothelium, Descemet's membrane, and posterior stroma were observed in the central cornea, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
1
32
0
5
Order By: Relevance
“…2 This hypothesis is consistent with recent findings that PITX2 expression in neural crest cells is observed not only in the anterior segment but also in the vitreous cavity at embryonic day 12.5 in mice. 3 Moreover, the deletion of 6p25, on which FOXC1 is located, which has a functional link with PITX2, 4 was reported to be associated with PHPV and Axenfeld-Rieger syndrome, 5 a syndrome thought to present the same spectrum of defects as Peters' anomaly.…”
Section: Conflict Of Interestsupporting
confidence: 82%
“…2 This hypothesis is consistent with recent findings that PITX2 expression in neural crest cells is observed not only in the anterior segment but also in the vitreous cavity at embryonic day 12.5 in mice. 3 Moreover, the deletion of 6p25, on which FOXC1 is located, which has a functional link with PITX2, 4 was reported to be associated with PHPV and Axenfeld-Rieger syndrome, 5 a syndrome thought to present the same spectrum of defects as Peters' anomaly.…”
Section: Conflict Of Interestsupporting
confidence: 82%
“…2 was performed out of cosmetic necessity, no similar patient has previously presented with an anterior staphylomatous mass from scleral thinning. Matsubara et al 5 suggested that maldevelopment of the iris stroma, ciliary stroma, goniodysgenesis, and typical coloboma as a result of a developmental disorder of neural crest cells causes an undifferentiated chamber angle, which is responsible for anterior staphyloma. Although the present case did not show coloboma of the uvea or sclera, we did confi rm the hypoplastic iris, ciliary body, and sclera.…”
Section: Discussionmentioning
confidence: 98%
“…30 In fact a mouse model has also been produced of this phenotype. 31 Whether the pathogenesis is due to a mechanical pushing forward of the lens or not, is at present unclear.…”
Section: Persistent Hyperplastic Primary Vitreousmentioning
confidence: 99%